2010
DOI: 10.1152/ajpheart.00691.2009
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac overexpression of the human 5-HT4receptor in mice

Abstract: Serotonin (5-HT) exerts pleiotropic effects in the human cardiovascular system. Some of the effects are thought to be mediated via 5-HT4 receptors, which are expressed in the human atrium and in ventricular tissue. However, a true animal model to study these receptors in more detail has been hitherto lacking. Therefore, we generated, for the first time, a transgenic (TG) mouse with cardiac myocyte-specific expression of the human 5-HT4 receptor. RT-PCR and immunohistochemistry revealed expression of the recept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

5
78
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 47 publications
(83 citation statements)
references
References 51 publications
(85 reference statements)
5
78
0
Order By: Relevance
“…In addition, they also demonstrated phosphorylation of PLB at Thr17, not a substrate for PKA but a substrate for calcium calmodulin kinase II (CaMKII). In hearts of 5-HT 4 TG mice, but not WT mice, 5-HT also increased the phosphorylation of PLB both at Ser16 and Thr 17 (Gergs et al 2010). Furthermore, basal phosphorylation of PLB at Thr17 in the absence of exogenous 5-HT in TG mice was increased in the ventricle of perfused hearts from TG mice and reduced by a 5-HT 4 receptor antagonist to levels of WT mice.…”
mentioning
confidence: 85%
See 4 more Smart Citations
“…In addition, they also demonstrated phosphorylation of PLB at Thr17, not a substrate for PKA but a substrate for calcium calmodulin kinase II (CaMKII). In hearts of 5-HT 4 TG mice, but not WT mice, 5-HT also increased the phosphorylation of PLB both at Ser16 and Thr 17 (Gergs et al 2010). Furthermore, basal phosphorylation of PLB at Thr17 in the absence of exogenous 5-HT in TG mice was increased in the ventricle of perfused hearts from TG mice and reduced by a 5-HT 4 receptor antagonist to levels of WT mice.…”
mentioning
confidence: 85%
“…5-HT, but hardly isoprenaline, also caused arrhythmic Ca 2+ transients in venricular myocytes from TG hearts. Interesting, in isolated hearts from these TG hearts Gergs et al (2010) demonstrated episodes of spontaneous polymorphic atrial arrhythmias in the absence of exogenous 5-HT that resemble shortlasting episodes of atrial fibrillation.In an additional report of Gergs et al (2013) in the present issue of Naunyn-Schmiedeberg's Archives of Pharmacology, the authors studied the effects of 5-HT on paced left atria and spontaneously beating right atria from their TG mouse. As expected, 5-HT produced sinoatrial tachycardia and increases in left atrial force, left atrial arrhythmias, phosphorylation of PLB at Ser16 and arrhythmias, which were antagonised by 5-HT 4 receptor blockers.…”
mentioning
confidence: 95%
See 3 more Smart Citations